Effect of Exercise Intervention on Craniovertebral Angle and Neck Pain in Individuals With Forward Head Posture in South Korea: Literature Review - Gyu-hyun Han; Chung-hwi Yi; Seo-hyun Kim; Su-bin Kim (Korean Research Society of Physical Therapy, 2023)
Forward head posture (FHP) is a musculoskeletal disorder that causes neck pain. Several exercise interventions have been used in South Korea to improve craniovertebral angle (CVA) and relieve neck pain. There has been no domestic literature review study over the past 5 years that has investigated trends and effects of exercise intervention methods for CVA with neck pain. This domestic literature review aimed to evaluate the trends and effects of exercise interventions on CVA and neck pain in persons with FHP. A review of domestic literature published in Korean or English language between 2018 and 2022 was performed. Literature search was conducted on Google Scholar and Korea Citation Index by using the following keywords: "exercise," "exercise therapy," "exercise program," "forward head posture," and "neck pain." Ten studies were included in this review. All of the studies showed positive improvements after intervention programs that included exercises. Notably, four of these studies demonstrated significant differences in results between the experimental and control groups. Among the 10 studies, nine measured visual analogue scale or numerical rating scale scores and reported significant reductions in pain following interventions, including exercise programs. Five of these studies showed significant differences in results between the experimental and control groups. Furthermore, six studies that used neck disability index exhibited a significant decrease in symptoms after implementing intervention programs that included exercise, and significant differences in results were found between the experimental and control groups. This domestic literature review provides consistent evidence to support the application of various exercise intervention programs to improve CVA and relieve neck pain from FHP. Further studies are warranted to review the effects of various exercise interventions on FHP reported not only in domestic but also in international literature.